2011
DOI: 10.1038/gt.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

In vivo therapeutic efficacy of intra-renal CD40 silencing in a model of humoral acute rejection

Abstract: The humoral branch of the immune response has an important role in acute and chronic allograft dysfunction. The CD40/CD40L costimulatory pathway is crucial in B-and T-alloresponse. Our group has developed a new small interfering RNA (siRNA) molecule against CD40 that effectively inhibits its expression. The aim of the present study was to prevent rejection in an acute vascular rejection model of kidney transplant by intra-graft gene silencing with anti-CD40 siRNA (siCD40), associated or not with sub-therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 43 publications
0
31
0
1
Order By: Relevance
“…Thus, studying the mechanisms by which this mechanism induces robust tolerance remains an important question for the field, with the aim of developing alternative methods of inhibiting CD154. Recent studies have used an RNAi approach to inhibit CD40 expression (41,42), and a similar approach could be envisaged for CD154 inhibition. Alternatively, non-cross-linking mAbs could be developed to antagonize CD154, much like nonactivating single-chain F V -based reagents have been developed in lieu of cross-linking anti-CD28 mAbs (43), which has resulted in a much more severe side effect profile than that seen in anti-CD154 mAbs in pilot studies in humans (44).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying the mechanisms by which this mechanism induces robust tolerance remains an important question for the field, with the aim of developing alternative methods of inhibiting CD154. Recent studies have used an RNAi approach to inhibit CD40 expression (41,42), and a similar approach could be envisaged for CD154 inhibition. Alternatively, non-cross-linking mAbs could be developed to antagonize CD154, much like nonactivating single-chain F V -based reagents have been developed in lieu of cross-linking anti-CD28 mAbs (43), which has resulted in a much more severe side effect profile than that seen in anti-CD154 mAbs in pilot studies in humans (44).…”
Section: Discussionmentioning
confidence: 99%
“…15,16,17,18,19,20 Additionally, recent work has demonstrated that patients at risk of recurrent FSGS have high plasma titers of CD40 autoantibodies which produce renal injury in mice. 21 These studies suggest that CD40 inhibition would have therapeutic value in the treatment of glomerulonephritis and related renal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…88-90 Targeting CD40 can also be achieved with small interfering RNA directed toward CD40 mRNA. 91,92 Finally, gene transfer of CD40Ig fusion proteins is also being explored, with contrasting results. 93,94 …”
Section: Cd40-cd40l Pathwaymentioning
confidence: 99%